METROLOGICAL MAINTENANCE OF SIMULATORS WITH MANY AMOUNTS OF FREEDOM - N. B. Sotsky (Приборы и методы измерений, 2015)
In article the applied aspects connected with use of a procedure of definition and record of a pose of the person for the analysis of biomechanical and physiological features of performance of power exercises with use of special simulators are considered. On the basis of carried out research the concept of frictional power simulators with many amounts of freedom is offered and realized.